The Influence of the Scramble Learning Model to Improve Student Learning Outcomes in Class V Science Subjects UPTD SD Negeri 125543 Pematang Siantar - Marihati Berliana Sitinjak; Natalina Purba; Sunggul Pasaribu (International Journal of Global Sustainable Research, 2023)
This study aims to see the effect of the scramble learning model to improve student learning outcomes in science subjects in class V UPTD SD Negeri 125543 Pematang Siantar. The research method used is quantitative with the type of Pre-Experimental Design research and One-Group Pretest-Posttest research design. The results of the average pretest score are 57.73 which is included in the poor category or has not met the KKM, then the average posttest result is 73.86 which is included in the good category. Based on the results of data analysis and hypotheses tested, it is known that the scramble learning model affects student learning outcomes. This is evidenced by the results of the t test with the type of paired sample t-test statistical test obtained the tcount price of 7.400 with a frequency (db) of 22-1 = 21, at a significant level α = 0.05, the ttable is 2.080, so the tcount> ttable or 7.400> 2.080 is obtained, H0 is rejected and Ha is accepted, which means that the hypothesis in this study Ha is accepted. Thus the scramble learning model has an effect on the learning outcomes of class V students UPTD SD Negeri 125543 Pematang Siantar.